THE ROLE OF INTERNAL AND EXTERNAL CONTEXTUAL FACTORS ON FIRMâS RESOURCES-PERFORMANCE RELATIONSHIPS - Ellitan, Lena (Kinerja: Jurnal Bisnis dan Ekonomi, 2013)
The critical resources affect the power of companyâs competitiveness. Management and business literaturehave limited knowledge and empirical research concerning the problems faced by the Indonesian manufacturingsector in relation to resources management, strategy, and environment issues. The broad objective of this studyis to investigate the effects of resources on performance in Indonesian manufacturing fi rms and to analyzesensitivity of the resource-growth relationship on the degree of competition, degree of uncertainty as well asfi rmâs characteristics. This study is conducted by distributing a set of structured questionnaires to the CEOs oflarge-scale manufacturing fi rms. Simple random sampling is used in this study in order to provide the least biasand offer most generalizability. This study indicates that for the Indonesian manufacturing fi rms to survive andto grow, they need not only to improve its production capacities but also technological capabilities. The effectsof fi rmâs resources on performance depend on contextual factors such as environment and business strategies.Keywords: Firmâs Resources, degree of competition, uncertainty, fi rmâs characteristic, fi rmâs performace.